Analyses of the 2019 Nobel Prize in Physiology or Medicine: Molecular Machinery for Cellular Oxygen Level Response. Issue 1 (2nd January 2020) - Gilman, Neyda V.
ABSTRACT: Gregg L. Semenza, William G Kaelin, Jr, and Sir Peter J. Ratcliffe were awarded the 2019 Nobel Prize for Physiology or Medicine on October 7, 2019. Their work led to the understanding of how cells recognize and adapt to varying oxygen levels. Hypoxia-inducible nuclear factors play an essential role in this mechanism by turning on other genes that work toward increasing oxygen levels in hypoxic environments. Other vital pieces of the machinery include von Hippel-Lindau proteins and prolyl hydroxylation. Due to the necessity of oxygen in numerous human physiological systems, this discovery will likely have nearly immeasurable impacts on human health.